PERSPEKTIF LITERASI KESEHATAN DAN NORMA SOSIAL TERHADAP PERNIKAHAN DINI DI KECAMATAN PETARUKAN - Indah Sari Damayanti; Muhamad Azinar (Jurnal Kesehatan Masyarakat, 2022)
Increasing early marriage during the pandemic can increase various health problems to mothers and children. In 2020 early marriage in Petarukan Subdistrict is 136 case. MMR cases in Regency (58.85 per 100,000 live births). The purpose of this study was to analyze the perspective of health literacy and social norms with early marriage. This type of research is quantitative with a case control design. The population in this study were 914 women in Petarukan District. Sample of 74 women, 37 cases and 37 controls, was taken by simple random sampling. Data were collected by questionnaire. Data analysis used chi square test with SPSS, univariate and bivariate. The results of the study found that early marriage can be controlled with good health literacy (97.3%). In social cognitive theory, a person's actions related to health are influenced by three factors, namely individual factors, environmental factors and behavioral factors. From the 2 variables, only health literacy is associated with early marriage. It can be seen that the health literacy of a person/individual can affect the incidence of early marriage. Then the social norms that occur in Petarukan District are only the customary customs of the community who marry their children at the age under of 19 years women who are not yet  getting married will often be asked by relatives  in his environment. Suggestions to the Health Office is to provide health information, delay of marriage age and marriage counseling held.